Pengaruh Layanan Konseling Kelompok Dalam Mengatasi Perilaku Merokok Pada Siswa SMA di Kota Palembang - Setiawati, Putri; Faulin, Delvina; Anindya, Violeta Ayu; Alfaroji, Muhammad Arif; Sari, Resti Okta (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to determine the effectiveness of group counseling services on smoking behavior of high school students in Palembang city. In this study researchers used descriptive qualitative research with data source sampling techniques in this study were snowball. The data collection techniques used in this study are interviews and documentation. The results of the implementation of group counseling showed a decrease in smoking frequency in some subjects, especially those with mild addiction. Based on the comparison of pre-test and post-test data, there was a significant increase in their understanding of the dangers of smoking, attitudes towards smoking behavior, and motivation to reduce smoking. This is evidenced by the average N-gain score recorded at 63.29%, indicating that group counseling with the role playing method is quite effective in reducing cigarette addiction. Overall, this study shows that a group counseling approach with role playing techniques can be effective to help adolescents reduce smoking habits and increase their awareness about the dangers of smoking.